Pengaruh Promosi Dan Harga Terhadap Keputusan Penyewaan Kamera Pada PT. Arah Media Kreasi Bogor - Maryati, Maryati; Wijaya, Muhamad Restu (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study is to determine the influence of promotion and price on camera rental decisions at PT. Arah Media Kreasi Bogor. This research uses a quantitative descriptive method with an associative approach. The sampling technique used is probability sampling, with sample selection based on the Slovin formula. The analysis methods include regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this study show that Promotion (X1) and Price (X2) have a significant influence on Rental Decision (Y), with the regression equation Y = 30.673 + 0.096 (X1) + 0.488 (X2) + α. The coefficient of determination shows a simultaneous influence of 18%. The partial hypothesis test for Promotion (X1) shows that tcount > ttable (3.239 > 1.290), indicating that H0 is rejected and H1 is accepted. This means there is a significant influence of the independent variable Promotion (X1) on Rental Decision (Y). The partial hypothesis test for Price (X2) shows that tcount > ttable (4.442 > 1.290), indicating that H0 is rejected and H2 is accepted. This means there is a significant influence of the independent variable Price (X2) on Rental Decision (Y). The simultaneous hypothesis test for Promotion (X1) and Price (X2) shows that Fcount > Ftable (9.965 > 2.360), indicating that H0 is rejected and H3 is accepted, which means Promotion (X1) and Price (X2) together have a significant influence on Rental Decision (Y).